The 2023 Baseball Trivia Extravaganza. - KEPNER, TYLER (New York Times, 2023)
The article focuses on the "Immaculate Grid," a baseball trivia quiz created by Brian Minter, offering a daily challenge to baseball enthusiasts and testing their knowledge of the sport's history, with the author presenting an annual trivia extravaganza.